MULTIGRADE TEACHING, A REMEDIAL STEP FOR SLOW LEARNERS IN AN INCLUSIVE SETUP - Tasneem Saifuddin; Dr. Waqas Bin Dilshad; Sonia Ishrat; Kanwal Shahzadi; Muhammad Altamash (International Journal of Contemporary Issues in Social Sciences, 2024)
In inclusive educational settings, the diverse learning needs of students often pose significant challenges, particularly for slow learners who may struggle to keep pace with their peers. This study explores the potential of multigrade teaching as an effective remedial strategy to support slow learners within an inclusive classroom environment. Multigrade teaching, where students of different ages and grade levels are taught together, offers a flexible and differentiated approach that can be tailored to meet the individual learning needs of students. Through action research, the study examines the effects of multigrade teaching on the academic performance, and social and emotional development of slow learners. Data is collected through student`s grade cards and through observation which was analyzed through SPSS conducting t- test and qualitative insights were gathered from classroom observations. The findings suggest that multigrade teaching not only fosters a supportive and collaborative learning environment but also allows for personalized instruction that benefits slow learners. The study concludes that multigrade teaching can be an effective remedial strategy, promoting the academic success and inclusion of slow learners in mainstream classrooms. Implications for educators and policymakers are discussed, with recommendations for the integration of multigrade practices in inclusive education frameworks.